"Liberalismo social", un modelo olvidado de la economía contemporánea - Rugina, Ángel (1955)
Liberty being indivisible, there is no political without economic liberty. In spite of many deficiencies, the free economy is superior to the planned economy. The ideal from would be the social liberalism in which the evils of both the capitalist as well as the socialistic systems would be cured by fundamental reforms of the public and private markets and of the banking, monetary and financing systems. All these reforms are possible and necessary if we want to live in a really free, democratic and stable economy and society.